URGENSI SANKSI PIDANA BAGI MUZAKKI YANG INGKAR MEMBAYAR ZAKAT DALAM RANGKA PENGEMBANGAN UNDANG-UNDANG ZAKAT DI INDONESIA - wahyuni, Fitri; Junaidi, Junaidi; Wandi, Wandi (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2023)
Zakat is one of the pillars of Islam and is one of the main elements for the upholding of Islamic law, whose obligations for Muslims have been stipulated in the Al-Qur'an, the Sunnah of the Prophet, and the consensus of the ulama. However, in reality, there are still many Muslims who are reluctant or refuse to pay zakat. This certainly requires efforts by imposing criminal sanctions so that the Muslim community becomes more aware of paying zakat. This research is normative legal research whose data is sourced from secondary data by collecting primary, secondary, and tertiary legal materials. Meanwhile, the analysis in this research uses qualitative analysis. Conclusions are drawn deductively. The urgency of criminal sanctions for muzakki who refuse to pay zakat in the framework of developing zakat law in Indonesia can be carried out in the following ways: 1. Internally within the Islamic community: First, building religious awareness that zakat is an instrument for alleviating poverty; Second, Unifying the opinion that based on sociological, philosophical, juridical, theological-normative, historical considerations or reasons, and the purpose of punishment, the application of criminal sanctions for muzakki is absolutely necessary; Third, fighting politically because political channels are one of the entry points for the application of Islamic law. 2. Government: First, build awareness that Indonesia's zakat potential is very large, while awareness of zakat is still small. So, the government should be proactive with the pick-up system by changing the zakat system from voluntary to mandatory (compulsory system); Second, the issue of zakat is an issue that applies specifically to the Muslim community. Thus, it would be better for the government to listen more to the aspirations of Muslims. Zakat merupakan salah satu rukun Islam, dan menjadi salah satu unsur pokok bagi tegaknya syariat Islam yang kewajibannya bagi umat Islam telah ditetapkan dalam Al-Qur’an, Sunnah Nabi, dan ijma’ para ulama. Namun pada kenyataannya masih banyak umat Islam yang enggan atau ingkar dalam membayar zakat. Hal ini tentu perlu upaya dengan memberlakukan sanksi pidana agar ummat islam lebih sadar lagi dalam membayar zakat. Penelitian ini merupakan penelitian hukum Normatif yang data-datanya bersumber data sekunder dengan mengumpulkan bahan hukum primer, sekunder dan tersier. Sedangkan analisa dalam penelitian ini menggunakan analisa kualitatif. Penarikan kesimpulan dilakukan dengan cara deduktif. Urgensi sanksi pidana bagi muzakki yang ingkar membayar zakat dalam rangka pengembangan undang-undang zakat di indonesia dapat dilakukan dengan cara 1. Internal Umat Islam: Pertama, Membangun kesadaran beragama bahwa zakat adalah salah satu instrument untuk mengentaskan kemiskinan; Kedua, Menyatukan pendapat bahwa berdasarkan pertimbangan atau alasan sosiologis, filosofis, yuridis, teologis-normatif, historis, dan tujuan pemidanaan penerapan sanksi pidana bagi muzakki mutlak dilakukan; Ketiga, Berjuang secara politik dikarenaka jalur politik merupakan salah satu pintu masuknya penerapan hukum Islam. 2.Pemerintah: Pertama, Membangun kesadaran bahwa potensi zakat Indonesia sangatlah besar, sedangkan kesadaran berzakat masih kecil. Sehingga, pemerintah seharusnya proaktif dengan sistem jemput bola dengan mengganti sistem zakat dari sukarela (voluntary system) menjadi wajib (compulsory system); Kedua, Persoalan zakat adalah persoalan yang berlaku khusus bagi ummat Islam. Dengan demikian, ada baiknya pemerintah lebih mendengarkan aspirasi umat Islam.